Phenotypic and genotypic characterization of Aeromonas jandaei involved in mass mortalities of cultured Nile tilapia, Oreochromis niloticus (L.) in Brazil - Assane, Inácio Mateus [UNESP]; de Sousa, Elielma Lima [UNESP]; Valladão, Gustavo Moraes Ramos; Tamashiro, Geovana Dotta [UNESP]; Criscoulo-Urbinati, Eduardo; Hashimoto, Diogo Teruo [UNESP]; Pilarski, Fabiana [UNESP] (Elsevier, 2021)
Aeromonas jandaei is an emerging fish pathogen associated with massive mortalities in cultured freshwater fish. This study investigated the morphological, biochemical, molecular, virulence, pathogenicity, and antimicrobial susceptibility characteristics of four strains of A. jandaei involved in the occurrence of mass mortalities of cultured Nile tilapia in an earthen pond farm and laboratory fibreglass tanks in Brazil. Isolates were identified by morphological, biochemical, and molecular analyses. Bacteria morphology was assessed under light and scanning electron microscopes, biochemical profile by conventional biochemical tests, and molecular identification by nucleotide sequencing and phylogenetic analysis of the highly conserved 16S rRNA gene, as well as the housekeeping genes, gyrB, and rpoB. The virulence and pathogenicity were confirmed by screening for 12 virulence genes and induced experimental infection. Broth microdilution method was used to assess susceptibility to enrofloxacin, florfenicol, oxytetracycline, and thiamphenicol. All isolates were confirmed as A. jandaei. Haemolysin, temperature-sensitive protease, haemolysin-aerolysin, and nuclease were the most predominant virulence genes. Lateral flagella B and cytolytic enterotoxin/cytotonic enterotoxin were only detected in strains isolated from fish from fibreglass tanks. In the experimental challenge, doses above 4.3 × 107 CFU mL−1 resulted in mass mortality (100%) in a short period (less than 12 h) without remarkable external clinical signs. Typical clinical signs of disease, including lethargy, inappetence, surface swimming, exophthalmia, cloudy eyes, haemorrhagic patches, and redness of the skin, below the opercula, and at the base of all fins, fin rot, and pale body surface were observed in fish challenged with doses below 4.0 × 107 CFU mL−1 (10–100% mortality). The most predominant histopathological changes in the internal organs of diseased fish were melano-macrophage centres, vascular congestion with thrombus, haemorrhage, and necrosis. Strains isolated from fish from the earthen pond farm were resistant to oxytetracycline, while the strains from fibreglass tanks were sensitive to all antimicrobials. This study provides pertinent data on A. jandaei host-pathogen interactions, susceptibility to antimicrobials, morphological, biochemical, and molecular characteristics, and geographical distribution, which may serve as a guideline for A. jandaei isolation and identification in aquaculture.
Keywords: Antimicrobial resistance; Bacterial infection; Housekeeping genes; Mass mortality; Scanning electron microscopy; Virulence